Impact of cisplatin dose and smoking pack-years in human papillomavirus–positive oropharyngeal squamous cell carcinoma treated with chemoradiotherapy. (September 2019) - Oliva, Marc; Huang, Shao Hui; Xu, Wei; Su, Jie; Hansen, Aaron R.; Bratman, Scott V.; Ringash, Jolie; Jang, Raymond; Cho, John; Bayley, Andrew; Hope, Andrew J.; Chen, Eric; et al.
Abstract: Background: To evaluate the impact of cisplatin cumulative dose (CDDP-D) and smoking pack-years (PYs) on cause-specific survival (CSS) and overall survival (OS) in human papillomavirus–positive (HPV+) oropharyngeal carcinoma (OPSCC) using the eighth edition tumour-node-metastasis (TNM) staging classification (TNM8). Patients and methods: We reviewed patients with HPV+ OPSCC treated with high-dose CDDP and intensity-modulated radiotherapy between 2005 and 2015 at Princess Margaret Cancer Centre. CSS and OS were compared according to CDDP-D <200/=200/>200 mg/m 2 stratified by TNM8. Results: A total of 482 consecutive patients were evaluated (stage I/II/III: N = 189/174/119; CDDP-D <200/=200/>200 mg/m 2 : N = 112/220/150). Median follow-up duration was 5.1 years (range: 0.6–12.8). Five-year CSS and OS differed by stages I/II/III: 96%/85%/88% ( p= 0.005) and 93%/84%/78% ( p = 0.001), respectively. Five-year CSS by CDDP-D <200/=200/>200 mg/m 2 was similar in stage I (98%/95%/95%, p = 0.74) and stage II (88%/84%/84%, p = 0.86) but different in stage III (76%/98%/84%, p = 0.02). Five-year OS by CDDP-D <200/=200/>200 mg/m 2 did not differ significantly among stages. In the multivariable analysis, CDDP-D <200 mg/m 2 did not influence CSS in the whole cohort versus = 200/>200 mg/m 2 ( p=0.53 / 0.79, respectively) but was associated with reduced CSS in stage III subgroup versus =200 mg/m 2 (=200 mg/m 2 versus < 200 mg/m 2 hazard ratio [HR] = 0.08; 95% confidence interval [CI]: 0.01–0.67; p = 0.02). Higher smoking PYs had no effect on CSS ( p = 0.34) but reduced OS in the whole cohort (HR = 1.14 [95% CI: 1.02–1.27], p= 0.01). Conclusion: CDDP-D correlated with neither survival nor disease-specific outcomes in this large and homogeneous HPV+ cohort, although reduced CSS was observed in stageIII HPV+ OPSCC receiving CDDP-D <200 mg/m 2 . Smoking PYs were negatively associated with OS but not with CSS. Highlights: Cisplatin cumulative dose has no impact on outcome in human papillomavirus–positive (HPV+) oropharyngeal cancers. Higher smoking pack-years affect overall survival but not cancer-specific survival. There was reduced survival in patients with stage III disease with total cisplatin dose <200 mg/m 2 . The 8th edition tumour-node-metastasis (TNM) stage grouping separates well survival in HPV+ disease. Chemoradiotherapy should remain the standard of care while awaiting prospective data.